HUMAN RESOURCES STIFIn SEBAGAI INOVASI MANAJEMEN SDM: DAMPAKNYA TERHADAP KINERJA KARYAWAN DI SEKOLAH ISLAM - Karasna, Danang; Diandra, Didip; Haikal, Fahri; Priyono, Agung (Management and Leadership Study Programme, 2025)
This study explores the application of the Human Resources (HR) STIFIn method as an innovative approach to human resource management in Islamic educational institutions, focusing on its impact on employee performance. STIFIn is a personality profiling method based on genetic intelligence, identifying five dominant